Effects of mowing and fertilization on soil quality in a semiarid grassland of North China. (29th December 2020) - Wang, Dong; Huang, Xudong; Qiao, Ning; Geng, Qingling; Liu, Yinzhan; Song, Hongquan; Yang, Zhongling; Liu, Chun; Wang, Gang
Abstract: Soil quality has been defined as the capacity to sustain biological productivity and maintain environmental quality. Mowing and fertilization may affect ecosystem function through numerous soil properties, especially in semiarid grasslands where plant growth is limited by nutrient availability. However, the effects of grassland management on the trade‐off between soil quality and plant community structure is still unclear. Understanding the effect of land use type on soil quality is essential to adopt proper grassland management practices for a specific region. Principal component analysis was used to calculate a soil quality index (SQI) with 18 variables under the following treatments: control, mowing, nitrogen addition, and mowing plus nitrogen addition in August 2017 in a typical steppe of North China. This study showed that nitrogen addition significantly increased SQI by 0.82, field water capacity by 3.77%, soil capillary porosity by 3.30%, and soil available nitrogen content by 13.85 mg kg −1, but reduced soil aggregate proportion by 3.07%, microbial biomass nitrogen content by 7.74 mg kg −1, arbuscular mycorrhizal fungi by 0.02 μmol g −1, the ratio of fungus to bacteria by 0.16, and the ratio of Gram‐positive bacteria to Gram‐negative bacteria by 0.13 across the mowing and unmowing treatments. Nitrogen addition could improve productivity by increasing the soil quality but reduce plant diversity of the grassland ecosystems. Mowing did not affect SQI and aboveground biomass. The results suggested that fertilization as grassland management improved soil quality and productivity, whereas mowing was a sustainable way to maintain plant diversity in this semiarid grassland.